PENGARUH MODAL KERJA TERHADAP PROFITABILITAS (Study Kasus Pada PT. Indosat Tbk) - Heri "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims (1) to find out level of cash turnover, inventory turnover and accounts receivable turnover in PT. Indosat Tbk (2) to find out the level of profitability PT. Indosat Tbk and (3) To determine the effect of working capital on profitability PT. Indoat Tbk.The research was conducted with an emphasis on quantitative data derived from the financial report of PT. Indosat Tbk period 2008-2012. From the analysis that has been done note that Cash turnover, inventory turnover and accounts receivable turnover are fluctuation. Profitability while also experiencing fluctuations.The multiple regression model used in this study, the test results in a partial (t test) showed that the only receivable turnover variable influence significantly to Return on Asset. While simultaneously (f test) show that cash turnover, inventory turnover and accounts influence Return on Asset.Keywords :Working Capital , Profitability, Return on Asset